Quantum dot light-emitting device, preparation method thereof and display device

By using absorbent material with HOMO energy level deeper than -5eV in the hole transport layer of the quantum dot light emitting device to absorb the destructive energy state, the problem of poor brightness stability is solved, and the brightness stability and life of the device are improved.

CN119173070APending Publication Date: 2024-12-20BOE TECHNOLOGY GROUP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310729371.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The brightness stability of quantum dot light emitting devices is poor, resulting in aging of luminous intensity.

Method used

Introduce absorber material into the hole transport layer of the quantum dot light emitting device to absorb the destructive energy state and prevent it from further propagating. By setting the HOMO energy level of the absorber material is deeper than -5 eV to match and absorb the destructive energy state in the high energy band. , reduce its damage to the main material.

Benefits of technology

It effectively improves the brightness stability of quantum dot light emitting devices, slows down the aging of luminous intensity, and ensures the long life and efficient performance of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173070A_ABST
    Figure CN119173070A_ABST
Patent Text Reader

Abstract

The invention discloses a quantum dot light-emitting device, a preparation method thereof and a display device, and relates to the technical field of display. The hole transport layer is arranged on one side of the quantum dot light-emitting layer, the hole transport layer at least comprises a main body material and an absorbent material, the absorbent material is used for absorbing a destroyed energy state, and the HOMO energy level of the absorbent material is deeper than-5eV.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the field of display technology, and specifically, to a quantum dot light-emitting device and a preparation method thereof, and a display device. Background Art

[0002] Quantum dots are a type of semiconductor nanocrystal that can be processed in a solution. They have the advantages of narrow luminescence spectrum, adjustable luminescence wavelength, and high spectral purity. They are most likely to become the core part of the next generation of light-emitting devices. Quantum dot light emitting diodes (QLEDs) use quantum dots as the material for the light-emitting layer, and introduce the light-emitting layer between different conductive materials to obtain the required wavelength of light. Their technical expertise comes from the advantages of high color gamut, self-luminescence, low starting voltage, fast response speed, and long life. It is a light-emitting display technology that is very close to commercialization in recent years. QLED is expected to enter the high-end display market first in the future, providing more accurate and vivid color performance than OLED. Summary of the invention

[0003] The embodiments of the present application provide a quantum dot light-emitting device and a method for preparing the same, and a display device, aiming to solve the problem of poor brightness stability of the quantum dot light-emitting device.

[0004] A first aspect of an embodiment of the present application provides a quantum dot light-emitting device, comprising:

[0005] Quantum dot light-emitting layer;

[0006] A hole transport layer is arranged on one side of the quantum dot light-emitting layer, and the hole transport layer at least comprises a main material and an absorber material, wherein the absorber material is used for absorbing the destructive energy state, and the HOMO energy level of the absorber material is deeper than -5eV.

[0007] In an alternative embodiment, the LUMO energy level of the absorber material is shallower than -3 eV.

[0008] In an optional embodiment, when the wavelength of light is less than or equal to 400 nm, the absorption intensity or absorption coefficient of the absorbent material is greater than or equal to 10 4 cm -1 .

[0009] In an optional embodiment, the HOMO energy level of the absorber material is deeper than the HOMO energy level of the host material.

[0010] In an optional embodiment, the LUMO energy level of the absorber material is shallower than the LUMO energy level of the host material.

[0011] In an optional embodiment, the purity of the absorbent material is greater than or equal to 97%.

[0012] In an optional embodiment, the mass fraction of the absorbent material in the hole transport layer is greater than or equal to 0.0001% and less than or equal to 90%.

[0013] In an optional embodiment, the mass fraction of the absorbent material in the hole transport layer is greater than or equal to 0.5% and less than or equal to 20%.

[0014] In an optional embodiment, the hole transport layer material includes at least one of the following: a mixture of the host material and the absorbent material, a polymer synthesized from the host material and the absorbent material, and a molecule synthesized from the host material and the absorbent material.

[0015] In an optional embodiment, the absorbent material includes any one or more of benzophenone and its derivatives, benzotriazole and its derivatives, triazone and its derivatives, salicylic acid and its derivatives, camphor and its derivatives, cyanoacrylate and its derivatives.

[0016] In an optional embodiment, the quantum dot light-emitting device further includes:

[0017] A cathode and an anode, wherein the quantum dot light-emitting layer is disposed between the cathode and the anode, and the hole transport layer is disposed between the quantum dot light-emitting layer and the anode;

[0018] A hole injection layer, the hole injection layer is disposed between the hole transport layer and the anode;

[0019] An electron transport layer is disposed between the quantum dot light-emitting layer and the cathode.

[0020] A second aspect of an embodiment of the present application provides a display device, comprising a quantum dot light-emitting device as described in any one of the first aspects.

[0021] A third aspect of the embodiments of the present application provides a method for preparing a quantum dot light-emitting device, the method comprising:

[0022] forming a quantum dot light-emitting layer;

[0023] A hole transport layer is formed on one side of the quantum dot light-emitting layer. The hole transport layer at least includes a host material and an absorber material. The absorber material is used to absorb the destructive energy state. The HOMO energy level of the absorber material is deeper than -5 eV.

[0024] In an optional embodiment, forming a hole transport layer on one side of the quantum dot light-emitting layer comprises:

[0025] A first target solution is spin-coated, and an annealing treatment is performed at a first preset temperature for a first preset time to form the hole transport layer on one side of the quantum dot light-emitting layer, wherein the first target solution is a mixed solution containing the main material and the absorbent material, or a solution containing a polymer synthesized from the main material and the absorbent material.

[0026] In an optional embodiment, forming a hole transport layer on one side of the quantum dot light-emitting layer comprises:

[0027] The host material and the absorbent material are simultaneously evaporated at different evaporation rates to form the hole transport layer on one side of the quantum dot light-emitting layer.

[0028] In an optional embodiment, forming a hole transport layer on one side of the quantum dot light-emitting layer comprises:

[0029] A second target solution is evaporated to form the hole transport layer on one side of the quantum dot light-emitting layer. The second target solution is a solution containing a synthetic material and the main material. The synthetic material includes molecules synthesized from the main material and the absorbent material.

[0030] Beneficial effects:

[0031] The present application provides a quantum dot light-emitting device and a preparation method thereof, and a display device, including: a quantum dot light-emitting layer; a hole transport layer, wherein the hole transport layer is arranged on one side of the quantum dot light-emitting layer, and the hole transport layer at least includes a host material and an absorbent material, wherein the absorbent material is used to absorb destructive energy states, and the HOMO energy level of the absorbent material is deeper than -5eV. The present application provides a hole transport layer containing an absorbent material to absorb carriers or excitons with high destructive energy states entering the hole transport layer, and converts them into a harmless state, thereby preventing further propagation of the destructive energy state, effectively improving the brightness stability of the quantum dot light-emitting device, and slowing down the aging of the luminous intensity of the quantum dot light-emitting device. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0033] Figure 1This is a schematic diagram of the structure of a quantum dot light-emitting device proposed in one embodiment of the present application;

[0034] Figure 2 This is a schematic diagram of the kinetic process of destroying energy states in a quantum dot light-emitting device proposed in one embodiment of the present application;

[0035] Figure 3 This is a typical UV-visible absorption spectrum of benzophenone and its derivatives proposed in one embodiment of the present application;

[0036] Figure 4 is a typical HOMO-LUMO energy level diagram of benzophenone and its derivatives proposed in one embodiment of the present application;

[0037] Figure 5 It is a typical HOMO-LUMO energy level diagram of benzotriazole, triazone and related derivatives proposed in one embodiment of the present application;

[0038] Figure 6 is a schematic diagram of preparing a hole transport layer by spin coating of a first target solution according to an embodiment of the present application;

[0039] Figure 7 This is a schematic diagram of another method of preparing a hole transport layer by spin coating of a first target solution proposed in an embodiment of the present application;

[0040] Figure 8 is a schematic diagram of preparing a hole transport layer by co-evaporation according to an embodiment of the present application;

[0041] Fig. 9 It is a schematic diagram of preparing a hole transport layer by single evaporation proposed in one embodiment of the present application.

[0042] Explanation of reference numerals: 100, cathode; 200, anode; 300, quantum dot light-emitting layer; 400, hole transport layer; 500, hole injection layer; 600, electron transport layer. DETAILED DESCRIPTION

[0043] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0044] In the related technology, quantum dots are a kind of semiconductor nanocrystals that can be processed in solution. They have the advantages of narrow luminescence spectrum, adjustable luminescence wavelength, and high spectral purity. They are most likely to become the core part of the next generation of light-emitting devices. Quantum dot light emitting diodes (QLEDs) use quantum dots as the material for the light-emitting layer, and introduce the light-emitting layer between different conductive materials to obtain the required wavelength of light. Its technical expertise comes from the advantages of high color gamut, self-luminescence, low starting voltage, fast response speed, and long life. It is a light-emitting display technology that is very close to commercialization in recent years. In the future, QLED is expected to enter the high-end display market first, providing more accurate and vivid color performance than OLED.

[0045] At present, there are still several unsurmounted technical barriers to the commercialization of QLED. One of them is the brightness stability of the device (used to measure the time required for the brightness of the device to decay to a certain percentage of the peak brightness). The destruction of the hole transport layer in the high-performance QLED system under the electrical operation of the QLED will cause a variety of effects, including causing the device operating voltage to increase, the carrier balance of the device to be destroyed, and the excited state of the light-emitting layer to be directly quenched by the hole transport layer (indicating that the number of photons generated during the fluorescence process decays or disappears in a shorter time). These effects come from the generation or injection of high-energy destructive energy states in the hole transport layer, which ultimately causes the luminous intensity of the quantum dot light-emitting device to age.

[0046] The traditional method to improve the brightness stability of QLED is mainly to adjust the electrical balance of the device, so that the destruction of energy states is minimized and enters the relatively fragile hole transport layer. Specific methods include reducing the energy disorder of the hole transport layer, adjusting the energy level matching of each layer structure, and improving the device injection characteristics. However, on the one hand, the stability of many systems is still not ideal; on the other hand, the hole transport layer itself is an organic semiconductor material. Due to the limitations of its bond energy, the improvement of its stability is limited. As a single material layer, the life performance of the QLED that can be prepared is limited. Especially for blue light QLED and pixelated QLED devices with poor thin film morphology, such ideal device characteristics are more difficult to achieve.

[0047] In view of this, the present application proposes a quantum dot light-emitting device. Figure 1 A schematic diagram of the structure of a quantum dot light-emitting device proposed in one embodiment of the present application is shown. Figure 1As shown, the quantum dot light emitting device comprises: a quantum dot light emitting layer 300 and a hole transport layer 400, wherein the hole transport layer 400 is arranged on one side of the quantum dot light emitting layer. The hole transport layer 300 comprises at least a host material and an absorber material, wherein the absorber material is used to absorb the destructive energy state, and the HOMO energy level of the absorber material is deeper than -5 eV.

[0048] In the embodiment of the present application, the destruction energy state includes carriers and excitons in a high-energy excited state, and the energy of the destruction energy state is greater than or equal to 2.7 eV. Figure 2 A schematic diagram of the dynamic process of destroying energy states in a quantum dot light-emitting device proposed in one embodiment of the present application is shown. Figure 2 As shown, under the electrical operation of the quantum dot light-emitting device, in addition to the generation of excited states of light emission, parasitic short-lived destructive energy states are also generated due to the influence of nonlinear effects (the operating voltage of the device becomes larger, the carrier balance is destroyed, the excited state of the quantum dot light-emitting layer is directly quenched by the hole transport layer, etc.), and these destructive energy states will have a considerable probability of impacting weak positions in the device during their life, such as the quantum dot light-emitting layer, the hole transport layer, and the interface between the quantum dot light-emitting layer and the hole transport layer. Exemplarily, in the hole transport layer, high-energy carriers and high-energy excitons undergo energy state quenching to generate destructive energy states; high-energy carriers and high-energy excitons in the quantum dot light-emitting layer undergo Auger recombination to generate destructive energy states, and these destructive energy states are gathered in the quantum dot light-emitting layer, the hole transport layer, and the interface between the quantum dot light-emitting layer and the hole transport layer.

[0049] Subsequently, the destructive energy state will be transferred to the hole transport layer. Since the hole transport layer is an organic semiconductor material and is the most easily damaged structure in the quantum dot light-emitting device, the destructive energy state generated in the quantum dot light-emitting layer, the hole transport layer, and the interface between the quantum dot light-emitting layer and the hole transport layer is transferred to the hole transport layer, and energy relaxation and regeneration occur in the hole transport layer to achieve storage of the destructive energy state (such as triplet aggregation). Finally, the destructive energy state stored in the hole transport layer destroys the material of the hole transport layer, generates defects, and further propagates the destructive energy state through chain cycles (such as free radical propagation).

[0050] In the embodiment of the present application, an absorbent material is added to the original organic semiconductor material (i.e., the main material) of the hole transport layer. The absorbent material interacts with the destructive energy state generated in the hole transport layer and the destructive energy state transferred to the hole transport layer, intervenes in the transfer process of the destructive energy state, and converts the energy of the destructive energy state into a harmless state, thereby reducing the storage amount of the destructive energy state, preventing the destructive energy state from damaging the main material, and effectively improving the brightness stability of the quantum dot light-emitting device.

[0051] Specifically, the absorbent material has a strong resonance intensity in the high energy band, so that the resonance intensity peak of the absorbent material matches the energy of the destruction energy state in the quantum dot light-emitting device, and no new hole traps are introduced. Therefore, the HOMO energy level of the absorbent material in the embodiment of the present application is deeper than -5eV. Preferably, the HOMO energy level of the absorbent material is deeper than -5eV, and the LUMO energy level of the absorbent material is shallower than -3eV. The absorbent material in this energy level range can ensure that it has a strong resonance intensity in the high energy band, and no new hole traps are introduced. For molecules or organic structures with relatively high resonance intensity, the energy of their action requires relatively rich energy bands and relatively high single-band transition state density. Therefore, for absorbent materials with strong resonance intensity, they will absorb specific high energy states. When the absorbent material with high resonance intensity corresponds to the energy of the trace electrical high energy state (i.e., the destruction energy state) in the quantum dot light-emitting device, it will cause effective absorption of the high energy state.

[0052] In an optional embodiment, when the wavelength of light is less than or equal to 400 nm, the absorption intensity or absorption coefficient of the absorbent material is greater than or equal to 10 4 cm -1 For absorbent materials, the absorption intensity of the absorbent material can be used to characterize its resonance intensity. The greater the absorption intensity of the absorbent material, the greater the resonance intensity. When the wavelength of light is less than or equal to 400nm, the absorption intensity of the absorbent material is greater than or equal to 10 4 cm -1 , it can be considered that the absorbent material has a strong resonance intensity in the high energy band. Preferably, when the wavelength of light is less than or equal to 400nm, the absorption intensity or absorption coefficient of the absorbent material is greater than or equal to 10 5 cm -1 Wherein, the resonance intensity of the absorbent material is expressed by the following equation:

[0053] f=4.319×10 -9 ∫ band dυε(υ)

[0054] Wherein ε(υ) is the absorption intensity of a specific molecule or group at wave number υ; and f is the resonance intensity of the absorbent material.

[0055] In an optional embodiment, in order to enable the added absorber material to effectively absorb the destruction energy state and improve the brightness stability of the quantum dot light-emitting device, it is also necessary to ensure that the absorber material does not have an adverse effect on the performance of the main material of the hole transport layer, thereby avoiding the efficiency performance of the quantum dot light-emitting device caused by the addition of the absorber material. Therefore, in the embodiment of the present application, the energy level of the absorber material must match the energy level of the main material of the hole transport layer while satisfying the requirement of having a strong resonance intensity in the high energy band and not introducing new hole traps (HOMO energy level deeper than -5eV), so as to ensure that the efficiency performance of the quantum dot light-emitting device will not be reduced due to the absorber material. Specifically, the HOMO energy level of the absorber material is deeper than the HOMO energy level of the main material. Preferably, the HOMO energy level of the absorber material is deeper than the HOMO energy level of the main material, and the LUMO energy level of the absorber material is shallower than the LUMO energy level of the main material. In addition, when the mass fraction of the absorber material in the hole transport layer is less than 0.5%, it is sufficient to ensure that the energy level range of the absorber material is sufficient so that the efficiency of the quantum dot light-emitting device does not significantly decrease due to the influence of the absorber material.

[0056] In an optional embodiment, since electrical devices are more affected by impurities than non-electrical devices, when the content of parasitic impurities in the absorber material accounts for a large proportion, the parasitic impurities will introduce new electron traps and hole traps, or accelerate or cause new electrical and electrochemical reactions, thereby negatively affecting the performance of the absorber material in absorbing and destroying energy states. Therefore, in an embodiment of the present application, the purity of the absorber material is greater than or equal to 97%. Exemplarily, the concentration of parasitic impurities in the absorber material can be obtained by testing methods such as nuclear magnetic resonance, mass spectrometry or cyclic voltammetry. The above-mentioned test method controls the concentration of parasitic impurities in the absorber material to be less than 3% (the purity of the absorber material is greater than or equal to 97%), so that the parasitic impurities in the absorber material do not cause a significant negative impact on the quantum dot light-emitting device.

[0057] In an optional embodiment, the absorbent material is added to the hole transport layer material, and is combined with the main material of the hole transport layer in a specific form to serve as the hole transport layer material. Therefore, in order to ensure that the absorbent material can effectively exert its absorption effect on the destructive energy state, the mass fraction ratio of the absorbent material in the hole transport layer is greater than or equal to 0.0001% and less than or equal to 90%. Preferably, the mass fraction ratio of the absorbent material in the hole transport layer is greater than or equal to 0.5% and less than or equal to 20%.

[0058] In an optional embodiment, the hole transport layer material includes at least one of the following: a mixture of the main material and the absorbent material, a polymer synthesized from the main material and the absorbent material, and a molecule synthesized from the main material and the absorbent material. Specifically, the hole transport layer material can be a mixture of the main material and the absorbent material. By using a mixture of the main material and the absorbent material, the technical difficulty and process cost caused by the synthesis of new materials can be avoided, and at the same time, the ratio between the main material and the absorbent material can be more effectively adjusted to improve the absorption effect.

[0059] The hole transport layer material can also be a polymer synthesized from the main material and the absorbent material. The polymer is a polymer polymerized from the main material monomer and the absorbent material monomer. The polymer can be a random dimer polymer, a diblock polymer or an alternating polymer. The application does not limit the polymerization form. Compared with the mixture, the hole transport layer material in the polymer form is more stable, and the absorbent material therein will not change with time, annealing conditions, etc., thereby maximizing the reduction of changes in the electrical properties of the hole transport layer caused by the diffusion of the absorbent material, and maximizing the absorption performance of the absorbent material. In addition, the hole transport layer material in the polymer form can effectively avoid the diffusion of the absorbent material to the adjacent layer, thereby reducing the negative impact of the absorbent material on the performance of the adjacent layer.

[0060] The hole transport layer material can also be a molecule synthesized from the main material and the absorbent material. Similar to polymers, the hole transport layer material in the form of a small molecule can improve the stability of the absorbent material, ensure the absorption performance of the absorbent material, and reduce the negative impact of the absorbent material on the performance of the adjacent layer. In addition, the hole transport layer material in the form of a small molecule can simplify the preparation process during the preparation process. For example, when the hole transport layer is prepared by an evaporation process, the synthesized small molecule hole transport layer material can be used to prepare the hole transport layer by a single evaporation process, reducing the preparation cost.

[0061] In an optional embodiment, the absorbent material includes any one or more of benzophenone and its derivatives, benzotriazole and its derivatives, triazone and its derivatives, salicylic acid and its derivatives, camphor and its derivatives, cyanoacrylate and its derivatives. Exemplarily, the absorbent material may be a substance represented by the following structural formula:

[0062]

[0063]

[0064] In an optional embodiment, the main material can be any one or more of 1,2,4,5-tetrakis(trifluoromethyl)benzene (TFB), poly(9-vinylcarbazole) (PVK), N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD), and 4,4'-di(9-carbazole)biphenyl (CBP).

[0065] Taking benzophenone and its derivatives as absorbent materials for hole transport layer as an example, Figure 3 The typical UV-visible absorption spectrum of benzophenone and its derivatives proposed in one embodiment of the present application is shown in FIG. Figure 3 As shown, benzophenone and its derivatives (such as Figure 3 The absorption intensity of the benzophenone and 3-hydroxybenzophenone shown in FIG. 1 is significantly increased when the wavelength of light is less than or equal to 400 nm, satisfying the absorption intensity or absorption coefficient greater than or equal to 10 4 cm -1 , it can be considered that the absorber material has a strong resonance intensity in the high energy band. Figure 4 The HOMO-LUMO energy level diagram of a typical benzophenone and its derivatives proposed in one embodiment of the present application is shown. Figure 5 The HOMO-LUMO energy level diagram of a typical benzotriazole and triazone and their related derivatives proposed in one embodiment of the present application is shown as follows: Figure 4 and Figure 5 As shown, benzophenone and its derivatives (such as Figure 4 The HOMO energy level of typical hydroxybenzophenone derivatives with different desubstitution groups shown in FIG) is deeper than -6.0 eV, and the LUMO energy level is shallower than -3 eV; typical benzotriazoles and triazinones and their derivatives (such as Figure 5 The HOMO of ethylhexyl triazone, diethylhexyl butyramido triazone and drometrizole trisiloxane shown in the figure is at an energy level of -6.0 eV, and the LUMO energy level is shallower than -2 eV. Therefore, when benzophenone and its derivatives, benzotriazole and triazone are used as the absorbent materials, their energy levels meet the requirements of having a strong resonance intensity in the high energy band, and no new hole traps are introduced, so that the destructive energy state can be effectively absorbed.

[0066] It should be noted that since the destruction energy states in quantum dot light-emitting devices exist in various forms (such as triplet states, doublet states, etc.), the density of these destruction energy states is usually relatively small, and it is difficult to directly measure them experimentally. Therefore, the brightness stability of quantum dot light-emitting devices based on the addition of absorbent materials needs to be calibrated by the stability in actual quantum dot light-emitting devices. The side reactions of the absorbent materials must also be compensated. The final effective combination can be a single type of absorbent material or a combination of multiple absorbent materials. The specific absorbent material can be determined according to the actual calibration situation, and this application does not limit it here.

[0067] In an optional embodiment, the quantum dot light emitting device further includes a first electrode 100, a second electrode 200, a hole injection layer 500 and an electron transport layer 600. Figure 1 Taking the quantum dot light-emitting device shown as an example, the first electrode 100 is a cathode, and the second electrode 200 is an anode. Among them, the first electrode 100, the second electrode 200, the hole injection layer 500 and the electron transport layer 600 can be made of suitable materials and using suitable processes, which is not limited in the present disclosure. Exemplarily, the anode can be any one or more of ITO, IZO, ITO / PEDOT (polymer of 3,4-ethylenedioxythiophene monomer), Ag, MoO3, etc.; the cathode can be any one or more of Al, ITO, etc.; the electron transport layer can be ZnO or Zn m X 1-m O, wherein X is any one of Mg, Al, and Y, and 0<m<1; the hole injection layer may be PEDOT (polymer of 3,4-ethylenedioxythiophene monomer):PSS (polystyrene sulfonate).

[0068] The present application provides a quantum dot light-emitting device, comprising: a quantum dot light-emitting layer; a hole transport layer, wherein the hole transport layer is arranged on one side of the quantum dot light-emitting layer, and the hole transport layer at least comprises a main material and an absorber material, wherein the absorber material is used to absorb the destructive energy state, and the HOMO energy level of the absorber material is deeper than -5eV. The present application arranges a hole transport layer comprising an absorber material to absorb carriers or excitons with high destructive energy states entering the hole transport layer, and converts them into a harmless state, thereby preventing further propagation of the destructive energy state, effectively improving the brightness stability of the quantum dot light-emitting device, and slowing down the aging of the luminous intensity of the quantum dot light-emitting device.

[0069] Based on the same inventive concept, an embodiment of the present application discloses a display device, which includes a plurality of quantum dot light-emitting devices as described in any one of the embodiments of the present application.

[0070] Based on the same inventive concept, an embodiment of the present application discloses a method for preparing a quantum dot light-emitting device, which is used to prepare the quantum dot light-emitting device described in the embodiment of the present application, and the method includes: forming a quantum dot light-emitting layer; forming a hole transport layer on one side of the quantum dot light-emitting layer, and the hole transport layer includes at least a main material and an absorber material, and the absorber material is used to absorb the destructive energy state, and the HOMO energy level of the absorber material is deeper than -5eV.

[0071] In an optional embodiment, the embodiment of the present application forms a hole transport layer by spin coating. Specifically, firstly, a first electrode is formed, and the first electrode is pretreated with ultraviolet ozone (UV Ozone), a hole injection material is spin coated on one side of the first electrode, and an annealing treatment is performed at a second preset temperature for a second preset time to form a hole injection layer; the device is transferred to an inert environment, a first target solution is spin coated, and an annealing treatment is performed at a first preset temperature for a first preset time to form the hole transport layer on the side of the hole injection layer away from the first electrode, wherein the first target solution is a mixed solution containing a main material and the absorbent material, or a solution containing a polymer synthesized from the main material and the absorbent material. It should be noted that the polymer is a polymer polymerized by a main material monomer and an absorbent material monomer, and the polymer can be a random dimer polymer, a diblock polymer or an alternating polymer, and the application does not limit the polymerization form.

[0072] Compared with the first target solution in the form of a mixed solution, the film layer prepared by the first target solution in the form of a polymer has a more stable component distribution, and the absorbent material therein will not change with time, annealing conditions, etc., thereby minimizing the change in the electrical properties of the hole transport layer caused by the diffusion of the absorbent material, and maximizing the absorption performance of the absorbent material; in addition, the first target solution in the form of a polymer avoids the diffusion of the absorbent material to the adjacent layer, thereby reducing the negative impact of the absorbent material on the performance of the adjacent layer.

[0073] After the hole transport layer is formed, the quantum dot light-emitting layer material is spin-coated on the side of the hole transport layer away from the first electrode, and annealing is performed at a third preset temperature for a third preset time to form the quantum dot light-emitting layer; the electron transport layer material is spin-coated on the side of the quantum dot light-emitting layer away from the first electrode, and annealing is performed at a third preset temperature for a third preset time to form the electron transport layer; finally, the second electrode is formed by vapor deposition on the side of the electron transport layer away from the first electrode.

[0074] Exemplarily, the host material is TFB, and the absorber material is 4,4,6,6-benzophenone. The quantum dot light-emitting device is prepared according to the following steps: using an ITO patterned substrate (ITO / PEDOT) as a first electrode, and performing UV Ozone pretreatment on the first electrode; spin coating PEDOT:PSS on one side of the ITO / PEDOT at a spin coating rate of 3000rpm / min, and annealing at 150°C in air for 30min to form a hole injection layer; Figure 6 FIG. 1 shows a schematic diagram of preparing a hole transport layer by spin coating of a first target solution according to an embodiment of the present application. Figure 6 As shown, the first target solution is a mixed solution containing a main material and the absorbent material. After forming the hole injection layer, the device is transferred to an inert environment, and the first target solution (mass concentration is 12 mg / ml, and the mass fraction ratio of the absorbent material is 1%) is spin-coated on the side of the hole injection layer away from the first electrode at a spin-coating rate of 2000 rpm / min, and annealed at 120°C in air for 10 minutes to form a hole transport layer; the quantum dot light-emitting layer material (mass concentration is 20 mg / ml) is spin-coated on the side of the hole transport layer away from the first electrode at a spin-coating rate of 2000 rpm / min, and annealed at 100°C in air for 10 minutes to form the quantum dot light-emitting layer; ZnO material is spin-coated on the side of the quantum dot light-emitting layer away from the first electrode at a spin-coating rate of 2000 rpm / min, and annealed at 100°C in air for 10 minutes to form the electron transport layer; finally, 100 nm Al is evaporated as the second electrode.

[0075] Exemplarily, the main material is TFB, the absorbent material is 4,4,6,6-benzophenone, and a first target solution is synthesized based on the main material and the absorbent material. The first target solution is a solution of a polymer synthesized from the main material and the absorbent material, and the general formula of the polymer is [A] x [B] y , wherein A is the main material TFB monomer, B is the absorbent material, x=200, y=2. The structural formula of the polymer is as follows:

[0076]

[0077] The quantum dot light-emitting device is prepared according to the following steps: using an ITO patterned substrate (ITO / PEDOT) as a first electrode, and performing UV Ozone pretreatment on the first electrode; spin coating PEDOT:PSS on one side of the ITO / PEDOT at a spin coating rate of 3000 rpm / min, and annealing at 150° C. in air for 30 minutes to form a hole injection layer; Figure 7FIG. 2 shows another schematic diagram of preparing a hole transport layer by spin coating of a first target solution according to an embodiment of the present application. Figure 7 As shown, after the hole injection layer is formed, the device is transferred to an inert environment, and the first target solution of the polymer (mass concentration is 12 mg / ml) is spin-coated on the side of the hole injection layer away from the first electrode at a spin coating rate of 2000 rpm / min, and annealed at 120°C in air for 10 min to form a hole transport layer; the quantum dot light-emitting layer material (mass concentration is 20 mg / ml) is spin-coated on the side of the hole transport layer away from the first electrode at a spin coating rate of 2000 rpm / min, and annealed at 100°C in air for 10 min to form the quantum dot light-emitting layer; ZnO material is spin-coated on the side of the quantum dot light-emitting layer away from the first electrode at a spin coating rate of 2000 rpm / min, and annealed at 100°C in air for 10 min to form the electron transport layer; finally, 100 nm Al is evaporated as the second electrode.

[0078] In an optional embodiment, the embodiment of the present application forms a hole transport layer by co-evaporation. Specifically, a first electrode is first formed, and the first electrode is pretreated with ultraviolet ozone (UV Ozone), an electron transport material is spin-coated on one side of the first electrode, and annealing treatment is performed at a third preset temperature for a third preset time to form the electron transport layer; the quantum dot light-emitting layer material is spin-coated on the side of the electron transport layer away from the first electrode, and annealing treatment is performed at a third preset temperature for a third preset time to form the quantum dot light-emitting layer; different evaporation rates are used to simultaneously evaporate the main material and the absorbent material to form the hole transport layer on the side of the quantum dot light-emitting layer away from the first electrode, wherein the evaporation rate of the main material is In the range of and the ratio of the evaporation rate of the main material to the evaporation rate of the absorbent material is between (1:1) and (1000:1), and the melting point of the absorbent material is less than or equal to 800°C to ensure that the absorbent material reaches an available evaporation rate; spin-coating a hole injection material on a side of the hole transport layer away from the first electrode, and performing an annealing treatment at a second preset temperature for a second preset time to form a hole injection layer; finally, vapor-depositing a second electrode on a side of the hole injection layer away from the first electrode.

[0079] Exemplarily, the host material is CBP, and the absorbent material is benzotriazole. The quantum dot light-emitting device is prepared according to the following steps: using an ITO patterned substrate as the first electrode, the first electrode is pretreated with UV Ozone; spin-coating ZnO material on one side of the first electrode at a spin coating rate of 2000rpm / min, and annealing in air at 100°C for 10min to form the electron transport layer; spin-coating quantum dot light-emitting layer material (mass concentration of 20mg / ml) on the side of the electron transport layer away from the first electrode at a spin coating rate of 2000rpm / min, and annealing in air at 100°C for 10min to form the quantum dot light-emitting layer; Figure 8 FIG. 1 shows a schematic diagram of preparing a hole transport layer by co-evaporation according to an embodiment of the present application. Figure 8 As shown, after forming the quantum dot light-emitting layer, CBP is used as the first evaporation source with an evaporation rate of 1 nm / min, and benzotriazole is used as the second evaporation source with an evaporation rate of 0.1 nm / min, and a total of 50 nm is evaporated to form the hole transport layer; PEDOT:PSS is spin-coated on the side of the hole transport layer away from the first electrode at a spin coating rate of 3000 rpm / min, and annealed at 150°C in air for 30 minutes to form a hole injection layer; finally, 3 nm / 100 nm of MoO3 / Ag is evaporated as the second electrode.

[0080] In an optional embodiment, the embodiment of the present application forms a hole transport layer by single evaporation of a second target solution. Specifically, firstly, a first electrode is formed, and the first electrode is pretreated with ultraviolet ozone (UV Ozone), an electron transport material is spin-coated on one side of the first electrode, and an annealing treatment is performed at a third preset temperature for a third preset time to form the electron transport layer; the quantum dot light-emitting layer material is spin-coated on the side of the electron transport layer away from the first electrode, and an annealing treatment is performed at a third preset temperature for a third preset time to form the quantum dot light-emitting layer; the second target solution is evaporated at a preset evaporation rate to form the hole transport layer on the side of the quantum dot light-emitting layer away from the first electrode; the hole injection material is spin-coated on the side of the hole transport layer away from the first electrode, and an annealing treatment is performed at a second preset temperature for a second preset time to form a hole injection layer; finally, the second electrode is formed by evaporation on the side of the hole injection layer away from the first electrode.

[0081] Wherein, the second target solution comprises a solution of a synthetic material and the main material, the synthetic material comprises a molecule synthesized from the main material and the absorbent material, the general formula of the synthetic material is AB, wherein A is the main material, B is the absorbent material, and the melting point of the synthetic material is less than or equal to 800°C to ensure that the synthetic material reaches an available evaporation rate. The mixed solution of the second target solution comprises the main material and the synthetic material mixed in a preset mass fraction ratio, and the components of the second target solution are expressed as: [A] x% Mixed [B] 1-x% .

[0082] Exemplarily, the main material is CBP, and the absorbent material is benzotriazole. Based on the synthetic connection of the main material and the absorbent material, a synthetic material is obtained, and the synthetic material and the main material are prepared according to a preset mass fraction ratio of x=50 to prepare a second target solution. The structural formula of the synthetic material is as follows:

[0083]

[0084] The quantum dot light-emitting device is prepared according to the following steps: using an ITO patterned substrate as a first electrode, and performing UV Ozone pretreatment on the first electrode; spin-coating a ZnO material on one side of the first electrode at a spin-coating rate of 2000 rpm / min, and annealing in air at 100° C. for 10 minutes to form the electron transport layer; spin-coating a quantum dot light-emitting layer material (with a mass concentration of 20 mg / ml) on the side of the electron transport layer away from the first electrode at a spin-coating rate of 2000 rpm / min, and annealing in air at 100° C. for 10 minutes to form the quantum dot light-emitting layer; Fig. 9 FIG. 1 shows a schematic diagram of preparing a hole transport layer by single evaporation according to an embodiment of the present application. Fig. 9 As shown, after the quantum dot light-emitting layer is formed, the second target solution with x=50 is taken as the evaporation source, the evaporation rate is 1nm / min, and 50nm is evaporated to form the hole transport layer; PEDOT:PSS is spin-coated on the side of the hole transport layer away from the first electrode, the spin coating rate is 3000rpm / min, and annealing is performed at 150°C in air for 30min to form a hole injection layer; finally, 3nm / 100nm MoO3 / Ag is evaporated as the second electrode.

[0085] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0086] Although the preferred embodiments of the present disclosure have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present disclosure.

[0087] Finally, it should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or terminal device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or terminal device. In the absence of further restrictions, the elements defined by the sentence "including a..." do not exclude the existence of other identical elements in the process, method, article or terminal device including the elements.

[0088] The above is a detailed introduction to a quantum dot light-emitting device and a preparation method and a display device provided by the present disclosure. Specific examples are used in this article to illustrate the principles and implementation methods of the present disclosure. The description of the above embodiments is only used to help understand the method and core ideas of the present disclosure. At the same time, for general technicians in this field, according to the ideas of the present disclosure, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present disclosure.

Claims

1. A quantum dot light-emitting device, characterized in that: include: Quantum dot light-emitting layer; A hole transport layer is arranged on one side of the quantum dot light-emitting layer, and the hole transport layer at least comprises a host material and an absorber material, wherein the absorber material is used for absorbing the destructive energy state, and the HOMO energy level of the absorber material is deeper than -5eV.

2. The quantum dot light-emitting device according to claim 1, characterized in that: The LUMO level of the absorber material is shallower than -3 eV.

3. The quantum dot light-emitting device according to claim 1, characterized in that: When the wavelength of light is less than or equal to 400 nm, the absorption intensity or absorption coefficient of the absorbent material is greater than or equal to 10 4 cm -1 .

4. The quantum dot light-emitting device according to claim 1, characterized in that: The HOMO energy level of the absorber material is deeper than the HOMO energy level of the host material.

5. The quantum dot light-emitting device according to claim 1, characterized in that: The LUMO energy level of the absorber material is shallower than the LUMO energy level of the host material.

6. The quantum dot light emitting device according to claim 1, characterized in that: The absorbent material has a purity greater than or equal to 97%.

7. The quantum dot light-emitting device according to claim 1, characterized in that: The mass fraction of the absorbent material in the hole transport layer is greater than or equal to 0.0001% and less than or equal to 90%.

8. The quantum dot light-emitting device according to claim 7, characterized in that: The mass fraction of the absorbent material in the hole transport layer is greater than or equal to 0.5% and less than or equal to 20%.

9. The quantum dot light emitting device according to claim 1, characterized in that: The hole transport layer material includes at least one of the following: a mixture of the host material and the absorbent material, a polymer synthesized from the host material and the absorbent material, and a molecule synthesized from the host material and the absorbent material.

10. The quantum dot light-emitting device according to any one of claims 1 to 9, characterized in that: The absorbent material includes any one or more of benzophenone and its derivatives, benzotriazole and its derivatives, triazone and its derivatives, salicylic acid and its derivatives, camphor and its derivatives, cyanoacrylate and its derivatives.

11. The quantum dot light emitting device according to claim 1, characterized in that: The quantum dot light emitting device further comprises: A cathode and an anode, wherein the quantum dot light-emitting layer is disposed between the cathode and the anode, and the hole transport layer is disposed between the quantum dot light-emitting layer and the anode; A hole injection layer, the hole injection layer is disposed between the hole transport layer and the anode; An electron transport layer is disposed between the quantum dot light-emitting layer and the cathode.

12. A display device, characterized in that: The display device comprises a plurality of quantum dot light-emitting devices as described in any one of claims 1 to 11.

13. A method for preparing a quantum dot light-emitting device, characterized in that: The method comprises: forming a quantum dot light-emitting layer; A hole transport layer is formed on one side of the quantum dot light-emitting layer. The hole transport layer at least includes a host material and an absorber material. The absorber material is used to absorb the destructive energy state. The HOMO energy level of the absorber material is deeper than -5 eV.

14. The method for preparing a quantum dot light-emitting device according to claim 13, characterized in that: The hole transport layer is formed on one side of the quantum dot light-emitting layer, comprising: A first target solution is spin-coated, and an annealing treatment is performed at a first preset temperature for a first preset time to form the hole transport layer on one side of the quantum dot light-emitting layer, wherein the first target solution is a mixed solution containing the main material and the absorbent material, or a solution containing a polymer synthesized from the main material and the absorbent material.

15. The method for preparing a quantum dot light-emitting device according to claim 13, characterized in that: The hole transport layer is formed on one side of the quantum dot light-emitting layer, comprising: The host material and the absorbent material are simultaneously evaporated at different evaporation rates to form the hole transport layer on one side of the quantum dot light-emitting layer.

16. The method for preparing a quantum dot light-emitting device according to claim 13, characterized in that: The hole transport layer is formed on one side of the quantum dot light-emitting layer, comprising: A second target solution is evaporated to form the hole transport layer on one side of the quantum dot light-emitting layer. The second target solution is a solution containing a synthetic material and the main material. The synthetic material includes molecules synthesized from the main material and the absorbent material.